(untitled) (International Journal of Health, Animal Science and Food Safety, 2018)
Feline diffuse iris melanoma (FDIM) is the most common primary intraocular neoplasm in cats. It is usually a malignant tumor, even if slowly progressive, thus representing an unique spontaneous model of the aggressive, although rare, human iris melanoma. In cats, the extent of the tumor within the eye, expressed as histological grade, is considered a good predictor of survival. In the context of the neoplastic cells-tumor microenvironment interaction, Matrix Metalloproteinase-9 (MMP-9) is an endopeptidase able to digest the extracellular matrix with involvement in tumor invasion . MMP-9 expression has been positively correlated with metastasizing behavior in human posterior uveal melanoma. The present study investigates the expression of MMP-9 in a caseload of formalin-fixed paraffin-embedded FDIMs in relation to the histological grade and mitotic index (MI) (threshold=7/10 hpf). Sixty-one samples of FDIM evaluated on light microscopy (Fig. 1) were selected (grade I n=22, grade II n=20, grade III n=19). Immunohistochemical staining with standard ABC method was performed using a mouse anti-MMP-9 antibody. Results were semi-quantitatively scored and compared by Mann-Whitney U test. MMP-9 was expressed in 59,1% grade I FDIM, 90,0% grade II and 80,0% grade III. Tumors with MMP-9 expression in more than 50% of neoplastic cells were 13,6% in grade I cases, 40,0% in grade II and 36,8% in grade III. MMP-9 was expressed in 71,4% of FDIM with MI≤7 and 92,3% of FDIM with MI>7. MMP-9 expression differed significantly between grade I and the other two grades, and between groups with low and high MI. In conclusion, intense expression of MMP-9 seems to correlate with the histological aggressiveness of FDIM.